Predictors of Response to Conventional Dmards In Rheumatoid Arthritis Patients Presenting In A Tertiary Care Hospital of Pakistan - Yasmin, Saira; Hashmi, Umm E Laila; Ahmed, Maryam; Firdus, Maimona; Perveen, Shahida; Salim, Babur (Pakistan Armed Forces Medical Journal, 2026)
Objective: Conventional disease modifying anti-rheumatic drugs (DMARDs) are the first line drugs in a conventional DMARDs in Pakistan.Study Design: Prospective cohort study.Place and Duration of Study: Rheumatology Department of FFH Rawalpindi, Pakistan from Oct 2023 to Mar 2024.Methodology:  We included 224 cases of treatment naïve early Rheumatoid arthritis with moderate to high disease activity. Disease activity was assessed by DAS28 CRP. Baseline data were collected for demographic, clinical parameters and serology. Treatment response was categorized into good (DAS28 CRP≤3.2) and poor response (DAS28 CRP >3.2) at 3 months after treatment with conventional DMARDS. Predictors of treatment response were assessed by logistic regression analysis.Results: Females constituted 196(87.5%) patients. 118(52.7%) patients were seropositive. At 3 months, 139(62.1%) achieved remission, 65(29%) low, and 20(8.9%) moderate disease activity. 204(91.1%) patients achieved good response. The response was dependent on baseline disease activity as measured in terms of change in DAS-28 CRP.Conclusion: Patients with higher BMI has poorer response to conventional DMARDs. Weight optimization may be important step in improving the response to DMARDs in patients with Rheumatoid arthritis.